The use of wastes (organic and inorganic) in land restoration in relation to their characteristics and cost. Issue 5 (May 2019) - Pérez-Gimeno, Ana; Navarro-Pedreño, José; Almendro-Candel, María Belén; Gómez, Ignacio; Zorpas, Antonis A
The great extent of degraded soils in southeast Spain makes it necessary to carry out restoration and rehabilitation strategies. In addition, the great amount of wastes produced need to be properly managed. Several types of wastes and amendments (organic and inorganic) can be applied for soil rehabilitation and land restoration. When large areas must be restored several aspects should be considered, such as availability of the waste, its characteristics, and transport. This research focuses on the characterization and the cost of 12 waste types and amendments (such as sewage sludge compost, brown peat, black peat, fertilized peat, earthworm humus, straw hay, palm tree leaves, pine bark, exfoliated vermiculite, expanded perlite, limestone outcrops, and volcanic crushed stones) obtained from four different sources. All of them were characterized following the UNE standards for soil amendments and the cost was obtained as a mean value of four different sources. The results indicate a great variability of properties between organic and inorganic materials, as was expected. Depending on the type of restoration, the characteristics, and the cost, the materials can be selected for an adequate purpose. Sewage sludge compost is a good alternative for application in large areas related to its characteristics (organic matter content and nutrient availability) and low cost. For inorganic amendments, natural limestone outcrops were the low-cost alternative. The use of both wastes (composted sewage sludge and limestone raw materials) for soil rehabilitation can facilitate the reduction of landfill disposal and add value for these wastes. Moreover, the results are very useful for scientists and engineers who deal with the development of rehabilitation and restoration strategies.